Liberal World Order in the Age of Disruptive Politics: A Southeast Asian Perspective - Moch Faisal Karim (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
There is no question that the current liberal world order faces yet another challenge. The upcoming challenge that we are about to confront is an exceptionally different kind of challenge. This challenge is the emergence of what I call a disruptive politics in the heartland of consolidated liberal states. The two main side effects of disruptive politics can be seen at both the domestic and international levels. Domestically, there is growing rise of populism in stable western democracies epitomized with the election of Donald Trump as President of the United States of America. Internationally, there is a growing rejection of globalization and integration, exemplified by the UK leaving the EU. Many commentators and pundits have observed that the rise of disruptive politics is the very threat to the liberal world order that could eventually cause it to collapse from within. While the side effects of disruptive politics should be addressed with caution; however, it is misleading to equate the disruptive politics with its side effects such as the rise of populism and the growing contend with the globalization. I would argue that disruptive politics is necessary for the survival of the liberal world order. Disruptive politics is a way to make us realize that liberal democracy is not perfect and we need to fix it. This essay explores the notion of disruptive politics and the challenge it poses. It begins by unpacking the notion. It then offers three insights on how to maintain the liberal world order in an age of disruptive politics.